(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Yurnaliza Y, Jamilah I, Hartanto A, Lutfia A. 2021. Screening of endophytic fungi from oil palm (Elaeis guineensis) in producing exopolysaccharides. Biodiversitas 22: 1467-1473. Exopolysaccharides (EPS) are microbial polysaccharides with a high biotechnological application in many fields due to their bioactivity and biocompatibility. Endophytic fungi are potential agents for producing EPS even though they remained under-exploited, especially those originating as indigenous strains from oil palm (Elaeis guineensis Jacq.). The present study reports on EPS production by a collection of endophytic fungi isolated from the petioles of oil palm under submerged fermentation. The culture medium was formulated with sucrose as C-source to trigger the secretion of EPS by the strains. Isolation of EPS was done through absolute ethanol precipitation in cold conditions. A total of 29 endophytic fungal strains was recovered from the foliar part of the plants. Molecular identification based on ITS-rDNA region and phylogenetic construction of each lineage revealed the dominant species from Pestalotiopsidaceae (syn. Amphisphaeriaceae), followed by Hypoxylaceae, Pleosporaceae, Didymosphaeriaceae, Sporocadaceae, and other minor families. In general, most isolates were ascomycetous fungi along with a basidiomycetous and zygomycetous fungus. After fermentation for 10 days, three fungal endophytes identified as Annulohypoxylon thailandicum P8 (Hypoxylaceae), Pseudopestalotiopsis simitheae P1 (Pestalotiopsidaceae), and Diaporthe eucalyptorum P11 (Diaporthaceae) secreted EPS higher in values than the others. The most prominent strain was A. thailandicum P8 with a yield of >50 mg/100 mL of filtrate solution. Based on FT-IR spectral analysis, the EPS product was detected to contain carboxyl, carbonyl, glycosidic bonds, and hydroxyl groups hereafter confirmed the characteristics of exopolysaccharides. The results demonstrated that the EPS may be evaluated for its bioactivity in a future study.